A quality assessment of Internet information regarding accelerated orthodontics - Demirsoy Kevser Kurt; Imamoglu Tugce; Buyuk Suleyman Kutalmış (Sciendo, 2021)
The aim of the present study was to evaluate the quality of information uploaded onto the Internet regarding accelerated orthodontics.